Impact of Colonial Institutions on Economic Growth and Development in India: Evidence from Night Lights Data - Priyaranjan Jha; Karan Talathi (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study the implications of two historical institutions, direct British rule, and the heterogeneous land tenure institutions implemented by the British, on disparity in present day development using district level data from India. Using nightlights per capita as a proxy for district level per capita income, we find that modern districts that were historically under direct British rule had 39.47% less nightlights per capita in 1993 relative to modern districts that were historically under indirect British rule. The large gap persists even after including other controls such as educational attainment, health, and physical infrastructure. Looking at the growth pattern during 1993 to 2013, directly ruled districts had a 1.84% lower annual growth rate compared to indirectly ruled districts. As well, directly ruled districts were converging at a rate of 2% per year while indirectly ruled districts were converging at a rate of 5.7% per year. Much of the development gap between areas under indirect rule and direct rule can be accounted for by the adverse effect of landlord-based revenue collection system in the directly ruled areas.
Keywords: O11; O43; P16; P51; 330; institutions; direct British rule; economic growth; nightlights per capita; land tenure system; economic development; human capital